An exploration of individual, social and material factors influencing water pollution mitigation behaviours within the farming community - Inman, A; Winter, M; Wheeler, R; Vrain, E; Lovett, A; Collins, A; Jones, I; Johnes, P; Cleasby, W (Elsevier, 2017)
Diffuse pollution of watercourses from agriculture represents a complex and persistent environmental problem in the UK. This paper provides insights into why UK policy interventions have had limited success to date, drawing on the disciplines of psychology, sociology and behavioural economics to more thoroughly understand farmer attitudes and behaviours towards pollution mitigation. Our analysis is based on eliciting the opinions of commercial farmers through a series of surveys and discussion groups in three catchments: the grassland dominated River Eden catchment; the arable dominated River Wensum catchment and the mixed farming area of the Hampshire River Avon catchment. Results strongly suggest that a fundamental shift in identities, normative behavioural beliefs and social norms is required within the farming community before mitigation behaviours become embedded. Simply offering financial incentives or imposing regulatory penalties is unlikely to achieve the desired results. Double loop learning has the potential to enable farmers to migrate from a productivist to a multifunctional outlook where pollution mitigation becomes internalised within a farm management system. Expert farm advisors will be required to facilitate this process.